The role of serum E-selectin level and E-selectin gene S128R polymorphism on the enlargement of renal cyst in patients with polycystic kidney disease: Genetic background of renal cyst growth - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 2020)
Background: To determine the role of E-selectin gene S128R polymorphism on the enlargement of renal cysts in patients with polycystic kidney disease (PKD). Materials and methods: 76 PKD patients with no comoibidity were enrolled in the study. Serum E-selectin levels were analyzed by enzyme-linked inununoabsoibent assay (ELISA). E-selectin gene S128R (561 A>C. rs: 5361) polymorphism was examined by polymerase chain reaction restriction fragment length (PCR-RFLP). Magnetic resonance imaging was performed at baseline evaluation and at the end of the 1st year to determine cyst enlargement and total kidney volume (TKV). Results: No significant difference was identified between AA genotype and AC or CC variants of E-selectin gene S128R polymorphism in terms of age, disease duration, baseline cyst volume, cyst volume at the 12th month, baseline dominant cyst volume, and dominant cyst volume at the 12th month. In contrast, a significant difference was determined between the groups with regard to the change of TKV (2.9 +/- 13.4 vs. 5.2 +/- 16.3 mm(3); respectively. p = 0.01). In the correlation analysis, the serum E-selectin level was significantly correlated to glucose, alanine transaminase, creatinine, calcium, phosphorus, total protein, albumin, and end diastolic volume (p = 0.0001, p = 0.001, p = 0.03, p = 0.021, p = 0.023, p = 0.002, p = 0.003, and p = 0.047, respectively). Multivariate logistic regression analysis demonstrated a 1.32-fold higher risk of cyst enlargement in patients with CC polymorphism when compared to AA genotype (p = 0.052), but not between AA and AC genotypes or CC and AC genotypes. Conclusion: PKD patients with CC variants of the E-selectin gene S128R polymorphism are at greater risk of cyst enlargement. The results of the present study should be confirmed with further studies with large sample size and longer duration of follow-up.
Keywords: polycystic kidney disease; total kidney volume; cyst enlargement; E-selectin; S128R polymorphism; ADHESION MOLECULES; RISK-FACTORS; P-SELECTIN; PROGRESSION; ASSOCIATION; INFLAMMATION; EXPRESSION; GENOTYPE; ENCODES; PROTEIN